2017
DOI: 10.1016/j.worlddev.2016.12.003
|View full text |Cite
|
Sign up to set email alerts
|

How Does Gender Affect Sustainable Intensification of Cereal Production in the West African Sahel? Evidence from Burkina Faso

Abstract: HighlightsWe examine gender differentials in technology adoption on individually managed cereal plots.Female plot managers are less likely to adopt yield-enhancing and soil-restoring strategy sets than male plot managers.The socio-cultural context and economic attributes of the technology set affect incentives to adopt.We demonstrate that plot manager characteristics do influence adoption decisions.Household resources affect male and female plot managers differently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
62
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 44 publications
9
62
0
3
Order By: Relevance
“…Employing a multivariate probit technique, these authors found that the adoption of modern inputs and organic fertilizer are complementary, but that factors driving the use of modern inputs differ from those driving the application of organic fertilizer. A recent study by Theriault et al (2017), also using a multivariate regression approach, produced similar findings in Burkina Faso.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…Employing a multivariate probit technique, these authors found that the adoption of modern inputs and organic fertilizer are complementary, but that factors driving the use of modern inputs differ from those driving the application of organic fertilizer. A recent study by Theriault et al (2017), also using a multivariate regression approach, produced similar findings in Burkina Faso.…”
Section: Introductionsupporting
confidence: 64%
“…A recent study by Theriault et al . (), also using a multivariate regression approach, produced similar findings in Burkina Faso.…”
Section: Introductionmentioning
confidence: 99%
“…Third, to the best of our knowledge, the contemporary literature on gender inclusion has focused on, inter alia, the nexus between financial inclusion and mobile money in SSA with a moderating role of gender and social networks (Bongomin, Ntayi, Munene, & Malinga, 2018), the participation of rural women in information technology programmes for agricultural development (Uduji & Okolo-Obasi, 2018, 2019a, 2019bUduji, Okolo-Obasi, & Asongu, 2019); gender gap prevalence in financial inclusion (Kairiza, Kiprono, & Magadzire, 2017), the importance of gender in science education (Elu, 2018), a model for the analysis of gender within the informal and financial productive sectors (Bayraktar & Fofack, 2018), the nexus between gender inequality and access to microfinance (Mannah-Blankson, 2018), the importance of gender in sustainable agricultural production (Theriault, Smale, & Haider, 2017), and the role of ICT in gender inclusion (Efobi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies from East and West Africa have found that men, male-headed households, and households with a higher proportion of men were more likely than women, female-headed households, and households with a higher proportion of women to participate in programs that promote the use of fertilizer (Chen et al 2011, Fisher and Kandiwa 2014, Karamba and Winters 2015, Theriault et al 2017, Lambrecht et al 2018. Particular barriers to women's use of fertilizer include lack of capital, credit, and equipment, as fertilizer is typically expensive.…”
Section: Agricultural Technology Promotionmentioning
confidence: 99%
“…Research from Malawi suggests that access to an input subsidy may reduce these barriers for women, if they are able to access the subsidy (Fisher and Kandiwa 2014). Likewise, research from Africa and South Asia has demonstrated that women are typically less likely than men to participate in initiatives promoting the use of improved seeds as a result of physical and cultural barriers to access as well as a lack of targeted extension services (Uduji and Okolo-Obasi 2018, Fisher and Kandiwa 2014, O'Brien et al 2016, Theriault et al 2017, Lambrecht et al 2018. One study from the Demographic Republic of the Congo did find, however, that women were much more likely to engage in the use of improved seeds when they were promoted by an extension service, as their cultivation was laborintensive but not as capital-intensive as fertilizer (Lambrecht et al 2018).…”
Section: Agricultural Technology Promotionmentioning
confidence: 99%